Squalene–polyethyleneimine–dynamic constitutional frameworks enhancing the enzymatic activity of carbonic anhydrase. Issue 10 (10th May 2022) - Su, Dan-Dan; Aissou, Karim; Zhang, Yan; Gervais, Virginie; Ulrich, Sebastien; Barboiu, Mihail
Abstract : Carbonic anhydrase is an essential enzyme that catalyzes the hydration/dehydration of carbon dioxide, which is highly relevant to carbon capture processes. It's encapsulation in dynameric capsules enhance its activity, durability and stability. Abstract : Carbonic anhydrase is an essential enzyme that catalyzes the hydration/dehydration of carbon dioxide, which is highly relevant to carbon capture processes. However, its efficient encapsulation in host materials is of utmost importance for the system performance (durability, stability, and efficiency). In this paper we demonstrate that polyethyleneimine–polyethylene glycol squalene constitutional nanoparticles PEI–DCFs, synthesized via reversible imine/amino-carbonyl chemistry, are efficient host matrixes for bovine carbonic anhydrase (bCA) encapsulation. This system showed an impressive one-order-of-magnitude-improved catalytic proficiency ( k cat / K m = 7396 M −1 s −1 ) as compared to bCA alone ( k cat / K m = 504 M −1 s −1 ). This performance rivals the current state-of-the-art systems with equivalent amounts of the enzyme, even after heating for a prolonged period at 80 °C, translating into its direct application for enhancing carbon dioxide capture and conversion.